2016
DOI: 10.1099/ijsem.0.001467
|View full text |Cite
|
Sign up to set email alerts
|

Apiotrichum terrigenum sp. nov., a soil-associated yeast found in both the UK and mainland Europe

Abstract: Five arthroconidium-producing yeast strains representing a novel Trichosporon-like species were independently isolated from the UK, Hungary and Norway. Two strains (Bio4T and Bio21) were isolated from biogas reactors used for processing grass silage, with a third strain (S8) was isolated from soil collected at the same UK site. Two additional strains were isolated in mainland Europe, one from soil in Norway (NCAIM Y.02175) and the other from sewage in Hungary (NCAIM Y.02176). Sequence analyses of the D1/D2 dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…A . montevideense is one of the causative agents of summer-type hypersensitivity pneumonitis [ 55 ], and was identified in a different unknown vertebrate microbiome ( Table 3 ). Apiotrichum domesticum , which causes the same disease [ 55 ], was identified in three mouse microbiomes ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A . montevideense is one of the causative agents of summer-type hypersensitivity pneumonitis [ 55 ], and was identified in a different unknown vertebrate microbiome ( Table 3 ). Apiotrichum domesticum , which causes the same disease [ 55 ], was identified in three mouse microbiomes ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…montevideense is one of the causative agents of summer-type hypersensitivity pneumonitis [ 55 ], and was identified in a different unknown vertebrate microbiome ( Table 3 ). Apiotrichum domesticum , which causes the same disease [ 55 ], was identified in three mouse microbiomes ( Table 3 ). FindFungi did not identify animal reservoirs for other significant human fungal pathogens such as Cryptococcus neoformans , Pneumocystis jirovecii , Coccidioides immitis , Histoplasma capsulatum , or Trichophyton rubrum .…”
Section: Resultsmentioning
confidence: 99%
“…These included the three black yeasts highlighted in this paper, H. werneckii, K. petricola, and A. pullulans. Two additional species were Apiotrichum dulcitum and A. porosum, which have only been recorded in terrestrial environments [95,96]. Both Apiotrichum species were isolated only from coastal sediment (legend continued on next page)…”
Section: Discussionmentioning
confidence: 99%
“…Concerning fungi, interestingly, our RF revealed that free-living unicellular fungi were indicators of evergreen forest plots. Yeasts like Solicoccozyma, Apiotrichum , and unclassified Saccharomycetales are commonly isolated from forest soils (Liu et al, 2015 ; Yurkov et al, 2015 ; James et al, 2016 ; Mašínová et al, 2016 ). However, our results showed their clear niche preference for the evergreen forests.…”
Section: Discussionmentioning
confidence: 99%